2024
DOI: 10.5267/j.uscm.2023.9.015
|View full text |Cite
|
Sign up to set email alerts
|

Environmental education using SARITHA-Apps to enhance environmentally friendly supply chain efficiency and foster environmental knowledge towards sustainability

Saritha Kittie Uda,
Basrowi Basrowi

Abstract: This study aimed to investigate the impact of Environmental Education on sustainability and the mediating role of Environmentally Friendly Supply Chain Efficiency (EFSC) and Fostered Environmental Knowledge (FENK). Employing a quantitative approach, data were collected from supply chain professionals who participated in Environmental Education programs. The research findings indicate a positive relationship between Environmental Education and supply chain sustainability. The study revealed that Environmental E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Recently, ref. [43] demonstrated that education has a significant positive impact on the sustainability of supply chains. Moreover, it contributes to promoting environmental knowledge and increasing chain efficiency supply.…”
Section: Environmental Sustainability Of the Supply Chain (Ensc)mentioning
confidence: 99%
“…Recently, ref. [43] demonstrated that education has a significant positive impact on the sustainability of supply chains. Moreover, it contributes to promoting environmental knowledge and increasing chain efficiency supply.…”
Section: Environmental Sustainability Of the Supply Chain (Ensc)mentioning
confidence: 99%